2020
DOI: 10.3329/bjb.v49i3.50009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical and antioxidant properties of edible fruits in the Sundarbans’ mangrove forest, Bangladesh

Abstract: Ten edible fruits of the Sunderbans’ mangrove forest in Bangladesh were analyzed to compare their physicochemical, nutritional and antioxidant properties. Among the fruits, the lowest pH of 4.2 was observed in Sonneratia caseolaris whereas the rest remains within 6.1 to 7.1. The highest electrical conductivity (596.3 μS/cm), total dissolved solid (298.2 ppm) and ash content (0.26%) were recorded in the fruit of Phoenix paludosa. Carbohydrate, protein, lipid and vitamin C contents were the highest in Avicennia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…However, moderate correlation (r 2 = 0.52) was found between total polyphenols and DPPH free radical scavenging. Hosen et al (2020) also reported similar results for edible fruits in the Sundarbans' mangrove forest of Bangladesh. This moderate correlation might be due to the involvement of specific phenolic and non-phenolic compounds in scavenging DPPH free radicals.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…However, moderate correlation (r 2 = 0.52) was found between total polyphenols and DPPH free radical scavenging. Hosen et al (2020) also reported similar results for edible fruits in the Sundarbans' mangrove forest of Bangladesh. This moderate correlation might be due to the involvement of specific phenolic and non-phenolic compounds in scavenging DPPH free radicals.…”
Section: Resultssupporting
confidence: 58%
“…E. officinalis showed the lowest IC 50 , which means that among these fruits it had the strongest DPPH scavenging activity. The IC 50 values for DPPH free radical scavenging of mangrove fruits (Hosen et al 2020), fruity vegetables (Hossain et al 2014) and leafy vegetables (Hossain et al 2015) were also reported. The highest reducing power, 1.98 (OD) was shown by E. officinalis at 1 mg powder/ml followed by G. cowa (OD, 0.4) (Table 1).…”
Section: Resultsmentioning
confidence: 95%
“…Mild heat treatments (60 • C, 30 min) on pawpaw pulp achieved 70% inactivation of PPO [92]. On the other hand, some authors [93] found that when blueberry purée was treated at different temperatures (40,50,60,70,80,90, and 100 • C) for 20 min the PPO activity decreased with increasing temperature. The activity was inactive when the processing temperature was higher than 80 • C. In addition, β-glucosidase activity was significantly decreased with increasing temperature.…”
Section: Conventional Methodsmentioning
confidence: 99%
“…Nowadays, the positive association between antioxidant activity and phytonutrients has been reported by various authors [ 79 ]. Other studies also found positive correlations, between antioxidant capacity and some bioactive compounds in various fruits [ 80 ] or in concrete fruits: doum [ 81 ], guava [ 82 ], black wolfberry [ 83 ], and strawberry [ 84 ]. Less correlation was exhibited in one article studying acerola, for vitamin C and total phenolic compounds [ 85 ], although one other work found a positive correlation only for ascorbic acid, also in acerola [ 86 ].…”
Section: Fruits and Their Antioxidant Activitymentioning
confidence: 95%
“…Secondary metabolites that are produced in the edible parts of the mangrove plants may be used to treat metabolic and infectious diseases in humans without inducing any toxic or hazardous effects. Previous reports have described physicochemical and antioxidant properties of the edible fruits Aegiceras corniculatum , Avicennia officinalis , Bruguiera gymnorrhiza , Ceriops decandra , Heritiera fomes , Nypa fruticans , Phoenix paludosa , Sarcolobus globosus , Sonneratia caseolaris , and Xylocarpus mekongensis , which are present in the Sundarbans mangrove forest ( Hosen et al, 2020 ). Moreover, studies have reported phytochemical and health promoting bioactivities of Sonneratia apetala fruits in the Sundarbans ( Hossain et al, 2013 ; Hossain et al, 2016 ; Hossain et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%